Political Armies : The Military and Nation Building in the Age of Democracy - Edited By Kees Koonings and Dirk Kruijt (London and New York Zed Books, 2002)
This is a comparative examination of the politicized armed forces of Peru, Burma, Chile, Turkey, Algeria, Ethiopia, Yugoslavia, Nigeria, and Guatemala. The volume looks at the consequences of military rule for nation building and economic development, and also addresses the effects the rise of globalization on the military, as well as the role of political armies in the consolidation of civil politics and democratic governance. The contributors provide a fascinating glimpse into the future, and make interesting connections between the role of the military and politics.
Include Index, Bibliograhy, Refrences, Notes and Abbrivations.
Keywords: Civil-Military Relations -- Economic Development